The soft power strategy for online tourism promotion in Saudi Arabia, applied to promotional videos on YouTube (International Journal of Financial, Administrative and Economic Sciences, 2026)
The study aimed to provide theoretical frameworks for a new media phenomenon by examining the concept of soft power, its mechanisms, tools, sources, and dimensions through the tourism film, how it is promoted, and presenting the identity of the film, which relies on digital applications on the Internet, along with showcasing Saudi soft power and its role in promoting tourism in Saudi Arabia. The study extracted tourism promotion films from YouTube as a sample to examine and study through the content analysis method. The study problem focused on how Saudi Arabia utilized soft power in tourism promotion.The study presented features of changing tourism promotion policies by analyzing the objectives of tourism promotion in the Kingdom and the soft power tools applied to achieve these goals through analyzing linguistic, auditory, and visual aspects of the films in terms of image and sound, and analyzing their content—how it was said and what was said, in addition to how soft power tools influenced tourism promotion in Saudi Arabia.The study concluded that soft power plays a role in promoting tourism, enhancing the Kingdom's status, and increasing its strength to achieve its objectives.
Keywords: Soft Power; E-Tourism Promotion; Saudi Arabia; Strategy